Gambaran Tingkat Kecemasan Pra Bencana Erupsi Gunung Merapi di Dusun Gebyog Selo Boyolali - Yahya Barlian Putra Al Janata; Siti Fatmawati (Galen: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Communities in Mount Merapi's hazard zones face significant pre-disaster anxiety due to recurrent volcanic activity and historical eruptions, yet specific profiles in high-risk hamlets remain underexplored. This study aimed to describe anxiety levels among residents of Dusun Gebyog, Selo, Boyolali, considering age, gender, education, and occupation. A descriptive quantitative design was employed with 78 respondents selected via consecutive sampling from a population of 356 adults aged 21-65. The Hamilton Anxiety Rating Scale (HARS) questionnaire assessed anxiety, analyzed univariately using frequency distributions in SPSS v.26. Results revealed moderate anxiety dominating (83.3%), followed by severe (9%), mild (6.4%), and panic (1.3%), with most respondents aged 21-35 years (39.7%), male (62.8%), high school educated (35.9%), and laborers (41%). In conclusion, while anxiety remains moderate due to prior experience and preparedness, targeted psychosocial interventions are essential to prevent escalation in vulnerable groups.